2020
DOI: 10.1101/2020.03.13.990424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trachomatous Trichiasis (TT) management in Tanzania: a mixed method study investigating barriers and facilitators to obtaining treatment

Abstract: 17 Background: Prolonged ocular Chlamydial infection, known as trachoma, can lead to trachomatous 18 trichiasis (TT). TT is the stage of trachoma where the eyelid turns inwards, resulting in lashes rubbing 19 against the cornea. TT can damage the cornea, leading to vision impairment or blindness. Treatment for 20 TT includes epilation or surgery. Trachoma is targeted for elimination as a public health problem. One 21 criterion of trachoma elimination is less than 0.2% prevalence of TT unknown to the health sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A qualitative study in Tanzania found that people were more reluctant to attend a surgical facility due to witnessing poor TT surgical outcomes of their neighbours. 21 Thus, prevalence of TT unknown to the health system in areas with historically high rates of PTT may reduce more slowly than other districts.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study in Tanzania found that people were more reluctant to attend a surgical facility due to witnessing poor TT surgical outcomes of their neighbours. 21 Thus, prevalence of TT unknown to the health system in areas with historically high rates of PTT may reduce more slowly than other districts.…”
Section: Discussionmentioning
confidence: 99%